Rice milling and parboiling trade-offs for economic and nutritional gains with special attention to sub-Saharan Africa: A comprehensive review - Ndindeng, Sali Atanga; Tang, Erasmus Nchuaji; Twine, Edgar; Taleon, Victor; Frei, Michael (Elsevier, 2025)
Rice is an important source of calories and nutrients for people in low- and middle-income countries. In the quest to respond to consumer preferences and attract premium prices, paddy processors increase the degree of milling (polishing), largely affecting nutritional composition and economic value of milled rice. Milling and parboiling are crucial unit processing operations affecting the quality profile of rice. The literature poorly reports on milling and parboiling operations that provide economic and nutritional gains or losses. Thus, there are no standard milling and parboiling regimes recommended to influence technological and policy changes in favor of public health and nutrition. In this comprehensive review, rice milling and parboiling operations associated with nutritional, economic, food safety and environmental benefits have been presented and discussed. Optimal milling and parboiling strategies that provide nutritional, economic, food safety and environmental gains are proposed as alternatives to conventional processing technologies and practices. Improved parboiling and moderate degree of milling in two-stage systems appear to provide better economic and nutritional benefits.